FROM THE EARS DOWN TO THE HEART: EXPLORING THE INFLUENCE OF MUSIC TRAILERS ON THE MUSIC STREAMING INTENTIONS OF GENERATION Z - Sekardhani, Mufida; Reyhan Adiva Ramadita; Satria Fadil Persada; Ni Gusti Made Rai (Bajang Institute, 2024)
Trailers have become a vital part of the film and music industries' marketing tactics, harnessing technological and media breakthroughs to attract audiences and raise enthusiasm for impending releases. Although studies on its impact in the film industry are diverse, there is limited knowledge regarding its significance in the music industry, particularly in music streaming services (MSS). The current study employs PLS-SEM to analyze the influence of music trailers on the intention to stream music in MSS, with data collected from 403 Gen Z respondents. The results suggest that understanding music trailers has positive effects on liking, which in turn leads to the intention to generate word of mouth and the intention to stream music on the respected music streaming platforms. Further discussion is provided on the theoretical contributions and practical implications.